Religious Rituals and Social Cohesion in Urban Societies: The Shift of Solidarity from Physical to Virtual Spaces - Muh. Ashabul Kahfi (Punggawa Global Research: Jurnal Multidisiplin, 2026)
This article examined how religious ritual supported social cohesion in urban settings and how solidarity was reshaped as participation shifted from physical communal space to virtual space. The study used a qualitative literature-based design relying on secondary data from recent scholarship in the sociology of religion, urban sociology, and mediated communication. The analysis compared predominantly physical, predominantly virtual, and hybrid ritual environments through three dimensions of solidarity: emotional attachment, moral commitment, and networked support. The findings indicated that physical rituals strengthened cohesion through embodied co-presence, informal social interaction, and locally visible accountability. Virtual rituals expanded access and accelerated coordination of support, but they also loosened membership boundaries and reconfigured authority through curation and platform dynamics, producing a more fluid form of affiliation. Hybrid patterns mitigated these trade-offs by combining the relational depth and accountability of in-person gathering with the accessibility and connective capacity of digital participation. The article concluded that solidarity persisted across spaces, but the mechanisms producing cohesion shifted from place-based reciprocity to connectivity-based participation.